EXODUS OF WHITE PEOPLE MINORITY FROM ANGOLA Adaptations to the Brazilian context. - Barreto, Isabel de Souza Lima (2012)
This paper aims to reflect about the process of adaptation of migrants who arrived in Brazil betweenthe end of 1974 and the year of 1976 because of the decolonization process of Angola. There are those whomigrated with their own resources directly to Brazil, there are those who lived a period in Portugal or in SouthAfrica before settling permanently in Brazil. When they arrived here, some found facilities in the process ofreception and adaptation. These are: relatives who lived in Rio de Janeiro, facilities created by the Braziliangovernment  to get  visas,  assistance  by institutions  of the  Portuguese community,  and  even  assistance  byunknown  persons.  There  are,  however,  who  has  gone  through  initial  difficulties.  To  give  a  bettercomprehension  of  the  arrival  of  these  immigrants,  we'll  do  references  to  the  colonial  war  and  to  thedecolonization process.